Supremasi Konstitusi dan Politik Legislasi KUHP Nasional: Analisis Hukum Tata Negara terhadap UU No. 1 Tahun 2023 - Riska Arianti; Wahyu Zaelani; Heri Sapari Kahpi; Nita Farhaturrahmah (Lex: Journal of Social Sciences and Humanities Perspectives, 2026)
The enactment of the New Indonesian Criminal Code through Law No. 1 of 2023 represents a significant milestone in the reform of national criminal law and reflects a strategic direction of Indonesia’s legal policy. However, as a comprehensive and codified statute, the New Criminal Code raises constitutional questions regarding its alignment with the principle of constitutional supremacy under the 1945 Constitution. This study aims to analyze the constitutional position of the New Criminal Code within Indonesia’s legal hierarchy and to examine the political-legal dynamics that shaped its legislative formation. Employing normative legal research with statute, conceptual, and historical approaches, this study analyzes primary, secondary, and tertiary legal materials using qualitative normative analysis and deductive legal reasoning. The findings reveal that while the New Criminal Code formally complies with the constitutional framework, several strategic provisions demonstrate potential tensions with constitutional principles, particularly in relation to freedom of expression, legal certainty, and the limitation of fundamental rights. Moreover, the legislative process of the New Criminal Code reflects a strong configuration of political power, ideological narratives, and limited substantive public participation, which affects its constitutional legitimacy. This study concludes that the constitutional validity of the New Criminal Code depends not only on its formal enactment but also on its substantive consistency with the values of constitutionalism. Strengthening constitutional review mechanisms and reorienting future criminal law legislation toward a more constitutionally grounded approach are essential to ensuring the supremacy of the Constitution in Indonesia’s legal system.